Child-Onset Cerebellar Ataxia Caused by Two Compound Heterozygous Variants in ADPRS Gene: A Case Report - Ma, Jiehui; Qian, Qiaoqiao; Yan, Shuang; Dou, Haoyu; Li, Cheng; Sun, Dan (Frontiers in Genetics, 2022)
Background: Gene variants of ADP-ribosylserine hydrosylase, also known as ADP-ribosylhydrolase-like 2 (ADPRS or ADPRLH2; OMIM: 610624), can cause stress-induced childhood-onset neurodegeneration with variable ataxia and seizures (CONDSIAS, OMIM: 618170), an ultra-rare neurodegenerative autosomal recessive disorder. ADPRS encodes ADP-ribosylhydrolase 3, which removes poly(ADP-ribose) polymers, whose posttranslational addition occurs under stressful conditions. Case Presentation: After a respiratory tract infection, a 30-month-old male patient presented with unsteady gait that rendered walking impossible without external help. Neurological examination revealed acute cerebellar ataxia, electroencephalogram results were abnormal, and brain magnetic resonance imaging revealed slightly widened cerebellar sulci. Laboratory tests showed decreased levels of thyroid-stimulating hormone, and increased levels of plasma lactic acid and serum cardiac enzymes. The cerebrospinal fluid glucose test was positive. Four months after onset, the patient died of sudden convulsions. Using whole exome sequencing, we identified two novel compound heterozygous ADPRS variants: NM_017825.3:c.580C>T (p.Gln194Ter) and NM_017825.3:c.803-1G>A. RNA sequencing indicated that the former mutation might cause nonsense-mediated mRNA decay. The c.803-1G>A variant was found to be a splice-site mutation that leads to the transcriptional retention of intron 5. According to the guidelines of the American College of Medical Genetics and Genomics, the two variants were classified as pathogenic. Conclusion: We present the first report of the existence of two compound heterozygous variants of ADPRS, which leads to CONDSIAS.